2013
DOI: 10.1111/hpb.12112
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival and incidence of hepatoblastoma in the paediatric population

Abstract: The incidence of paediatric HB has increased over time. Hepatoblastoma is almost exclusively seen in children aged < 5 years. When HB presents after the age of 5 years, the prognosis is most unfavourable. Tumour extirpation markedly improves survival in paediatric patients with local disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 34 publications
8
110
5
Order By: Relevance
“…54 The 5-year survival probability for hepatoblastoma patients in Germany (,15 years) was lower than that for French children in 2000-2008 51 but markedly better than in the United States for patients aged ,20 years in 1973-2009. 38 The survival also exceeded the probabilities reported for European children in 1978-1997. 15 However, the 1988-1997 probabilities in northern Europe were superior to the German ones, but the patient numbers were much lower, possibly enabling chance findings.…”
Section: -2004mentioning
confidence: 73%
“…54 The 5-year survival probability for hepatoblastoma patients in Germany (,15 years) was lower than that for French children in 2000-2008 51 but markedly better than in the United States for patients aged ,20 years in 1973-2009. 38 The survival also exceeded the probabilities reported for European children in 1978-1997. 15 However, the 1988-1997 probabilities in northern Europe were superior to the German ones, but the patient numbers were much lower, possibly enabling chance findings.…”
Section: -2004mentioning
confidence: 73%
“…It affects approximatively 1:1,000,000 children under the age of 15 and most predominantly between 6 months and 3 years (1,2). It has been reported that the risk of developing hepatoblastoma is increased in subjects that are afflicted by several syndromes, such as Beckwith-Wiedemann syndrome (BWS) (3), hemihypertrophy or familial adenomatosis polyposis (FAP) (4).…”
Section: Abstract Hepatoblastoma Is the Most Common Pediatric Livermentioning
confidence: 99%
“…HBL is classified into several histologic subtypes that recapitulate the different stages of liver development 2, 3. Chemotherapy associated with tumor resection or liver transplantation is the cornerstone of HBL treatment, resulting in a 5‐year patient survival of over 80% 1, 4. Cisplatin used alone or in combination with carboplatin or doxorubicin is generally very effective except for a few chemoresistant tumors.…”
Section: Introductionmentioning
confidence: 99%